The Influence of Financial Literacy on Customers' Ability to Avoid Phishing: A Case Study of Bank Syariah Indonesia Ahmad Yani Bone Branch Office - Edi Darnadi; ⁠Muh. Hasbi Ash. Shiddiq; Jumriani Jumriani (Jurnal Multidisiplin Sahombu, 2026)
This study aims to determine the influence of financial literacy on customers' ability to avoid phishing attacks and the extent to which financial literacy influences customers' ability to avoid phishing attacks at Bank Syariah Indonesia's Ahmad Yani Bone Branch. This study used a quantitative approach, using a questionnaire as the data collection method. The sample consisted of 50 customers of Bank Syariah Indonesia's Ahmad Yani Bone Branch. The data were collected through validity testing, reliability testing, classical assumption testing, and hypothesis testing. The results show that financial literacy has a significant influence on customers' ability to avoid phishing attacks at Bank Syariah Indonesia's Ahmad Yani Bone Branch. This is indicated by the R² value of 67.7%. This means that financial literacy is largely influenced by customers' ability to avoid phishing, while the remaining 32.3% is influenced by other factors. Therefore, the higher the financial literacy, the better the customer's ability to protect themselves from digital fraud.